Does caffeine consumption during pregnancy increase the risk of fetal mortality? A literature review - Alicia Matijasevich; Iná S. Santos; Fernando C. Barros
The aim of this study was to evaluate the available epidemiological evidence of the effect of caffeine consumption during pregnancy on fetal mortality. A systematic qualitative review of observational studies that referred to any source of exposure to caffeine from food in pregnancy and to fetal mortality as the outcome was conducted in the databases MEDLINE and LILACS. Studies published between January 1966 and September 2004 were searched. The following descriptors were used: "caffeine", "coffee", "tea", "cola", and "cacao" to define the exposure and "fetal death", "stillbirth", "fetal demise", and "fetal loss" to define the outcome. The search strategy retrieved 32 publications, but only six met the inclusion criteria and three were included. One more article was found using "see related articles" feature in PubMed. A total of four publications were included in the review. The small number of publications addressing this subject, methodological limitations, inaccurate exposure assessment in all the studies, overall risks only marginally significant in most cases, and the possibility of publication bias preclude stating with certainty that caffeine consumption is actually associated with fetal death.